Atypical multiple myeloma in 3 young dogs. Issue 5 (September 2022) - Wachowiak, Ian J.; Moore, A Russell; Avery, Anne; Magunda, Forgivemore; Harris, Adam; Laurence, Hannah; Fulkerson, Christopher M.; Fulkerson, Caroline V.; Messick, Joanne B.; Strandberg, Natalia J.; McGrath, Stephanie
Three dogs under 12 months old were diagnosed with atypical multiple myeloma (MM), having an aggressive multifocal anaplastic round cell sarcoma in bone marrow, viscera, and/or peripheral blood, which were confirmed by cytology and immunohistochemistry to be of plasma cell origin. The intramedullary sarcomas caused myelophthisis, osteolysis, and hypercalcemia. Complete or free light chain monoclonal gammopathy in the serum and/or urine was demonstrated by protein electrophoresis and immunofixation. The polymerase chain reaction for antigen receptor rearrangement assay performed on 2 cases identified a clonally rearranged immunoglobulin gene. Neoplastic cells lacked expression of CD45, CD3, CD18, CD21, CD34, and MHCII by flow cytometry. Immunohistochemistry revealed MUM1 immunoreactivity of the neoplastic cells. Combining all data, the diagnosis was MM. An aggressive form of MM in young dogs should be a differential diagnosis for patients with an immunoglobulin-productive, B cell-clonal, CD45-negative, MUM1-positive discrete cell neoplasm arising from the bone marrow.